GAMBARAN FUNGSI KOGNITIF PADA LANJUT USIA (LANSIA) - Andria Pragholapati; Firna Ardiana; Lia Nurlianawati (Jurnal Ilmiah Keperawatan, 2021)
Indonesia is among countries that entered the aging structured population because there were 7.18% of 60 year over Eldrly population. The increases of Elderly population caused some problems. The biggest problem in Elderly was degenerative diseases, physical changes appeared when people grow old. One of those changes was in anatomy and atrophy neurological system which is progressively decrease the cognitive function. Cognitive function was an ability to think, to remembered, to learned, to communicated, and to solved problem. The purpose of this research was to describe cognitive function, and used descriptive design research. This study design was kuantitatif deskriptif. Engineering sampling using purposive sampling. The population of this research was 56 people (34 in Panti Jompo Muhammadiyah and 22 in Yayasan Pondok Lansia Tulus Kasih) and almost 36 people participated. The data collecting technique used MoCA Ina questionnaire with univariate frequence using distribution analysis. The result showed almost half of them (47.2%) suffetred dementia alzheimer of severed cognitive disorder. Based on this research suggested to Panti manager to make efforts to increases cognitive function of Elderly such as brain gym and a relaxing way.